2013
DOI: 10.1097/brs.0b013e318263bb7b
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Prolonged Disability in Patients With Chronic Low Back Pain and Lumbar Degeneration in Primary Care

Abstract: Increased pain-related disability at 1 year was seen in patients with impaired fasting glucose tolerance, greater pain-related disability, higher BMI, and lower quality of life at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 72 publications
1
25
1
Order By: Relevance
“…Nevertheless, the current literature about the association of Modic changes and low back pain (as well as the predictive value of Modic changes upon surgical outcomes after lumbar fusion) is still very controversial, with several studies suggesting that no meaningful association exists [55].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the current literature about the association of Modic changes and low back pain (as well as the predictive value of Modic changes upon surgical outcomes after lumbar fusion) is still very controversial, with several studies suggesting that no meaningful association exists [55].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The association between longer duration of pain and poorer prognosis is consistent with the findings in cohort studies that greater disease burden in general (eg, higher baseline pain scores and disability) predicts poorer outcomes for spinal pain. [15][16][17] Neck pain can also be categorized by mechanisms as mechanical, neuropathic, or secondary to another cause (eg, referred pain from the heart or vascular pathology). Mechanical pain refers to pain originating in the spine or its supporting structures, such as ligaments and muscles.…”
Section: Classification Of Neck Painmentioning
confidence: 99%
“…Moreover, the persistence of the M1 component correlates with persistence of symptoms [13]. However, recently the clinical relevance of MC has been questioned, as in prospective studies, MC were not indicated as having any prognostic role in future low back symptoms [14,15]. …”
Section: Introductionmentioning
confidence: 99%